2018
DOI: 10.1017/s0954579418001104
|View full text |Cite
|
Sign up to set email alerts
|

Cultural neurobiology and the family: Evidence from the daily lives of Latino adolescents

Abstract: Culturally linked family influences during adolescence are important predictors of health and well-being for Latino youth, yet few studies have examined whether these familial influences are associated with indicators of typical physiological stress processes. Following a cultural neurobiology framework, we examined the role of family in the everyday lives of Latino adolescents (N = 209; Mage = 18.10; 85.1% Mexican descent; 64.4% female) by investigating familism values and perceptions of parent support as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 130 publications
(208 reference statements)
1
38
1
Order By: Relevance
“…In summary, while the experience of language brokering may activate stress biology, recovery from this stress response may vary based on individual and interpersonal contexts. Using the same sample as (Doane et al., 2018), a separate article examined links between cultural values and waking and diurnal cortisol activity (Sladek, Doane, Gonzales, Grimm, & Luecken, 2019). In this study, higher host (United States) cultural values were associated with higher waking cortisol and steeper diurnal cortisol slopes, a pattern interpreted to be adaptive in physiologically preparing individuals to respond to anticipated daily demands.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, while the experience of language brokering may activate stress biology, recovery from this stress response may vary based on individual and interpersonal contexts. Using the same sample as (Doane et al., 2018), a separate article examined links between cultural values and waking and diurnal cortisol activity (Sladek, Doane, Gonzales, Grimm, & Luecken, 2019). In this study, higher host (United States) cultural values were associated with higher waking cortisol and steeper diurnal cortisol slopes, a pattern interpreted to be adaptive in physiologically preparing individuals to respond to anticipated daily demands.…”
Section: Methodsmentioning
confidence: 99%
“…While acculturation is also typically discussed as a risk factor, biculturalism and ERI affirmation are promising as promotive factors for acculturating adolescents, and their positive effects on adjustment may be transmitted through stress biology. Interestingly, two studies found no associations between reported familism values and HPA axis functioning (Doane et al., 2018; Gonzales, Johnson, et al, 2018). However, one of these studies (Doane et al., 2018) did find that specific beliefs and practices associated with familism , such as family assistance behaviors, showed meaningful associations with cortisol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another domain of research on culture and biology interplay represented in this Special Issue is cultural neurobiology, or the study of the transactions among cultural processes and stress-sensitive neurobiology across development, including the autonomic nervous system, the hypothalamic–pituitary–adrenal axis, and the immune system (Doane, Sladek, & Adam, 2018). Doane, Sladek, Breitenstein, and colleagues (2018) investigated whether familial influences were associated with indicators of typical physiological stress processes with a sample of 209 Latino adolescents. They examined familism values, perceptions of parent support, and daily family assistance behaviors in relation to hypothalamic–pituitary–adrenal axis diurnal patterns, indexed by salivary cortisol five times a day for three days.…”
Section: Investigating the Interplay Of Culture And Biology In Develomentioning
confidence: 99%